Dukungan Keluarga Berpengaruh terhadap Tingkat Kecemasan pada Pasien Pre Operasi: Family Support Influences Preoperative Patient Anxiety Levels - Wiwi Wahyuni; Lannasari; Solehudin (MPI Press, 2022)
Introduction: Patients who will undergo surgery will have feelings of anxiety or anxiety such as fear or feelings of restlessness and worry, this anxiety can be seen from family support, namely family members who are active in reducing anxiety levels. Objective: This study aims to determine the relationship between family support and anxiety levels in preoperative patients. Methods: This study used a quantitative cross-sectional study, the sample in this study was 129 respondents, the instrument in this study used a family support questionnaire and a standardized HARS anxiety level questionnaire. Analysis using Spearman's Rank test. Results: The results of the univariate study showed that 25.6% of the age group were 26-35 years old, the highest number of females gender was 55% and the type of major surgery was 45.7%. The results obtained were 60.5% high family support and 31.8%. respondents experienced a moderate level of anxiety, then from the bivariate results of family support with a level of anxiety using the Spearman's Rank test with p-value = 0.000, which means p-value <0.05 with a correlation coefficient of 0.420. Conclusion: There is a relationship between family support and anxiety levels in preoperative patients.